SPAIN: PROBLEMS OF CONSOLIDATED DEMOCRACY IN A СOMPARATIVE HISTORICAL CONTEXT - S. M. Khenkin (Сравнительная политика)
Present-day Spanish society is suffering from political institutional  crisis raising vivid cutting-edge discussions on its sources. Widely  spread is the viewpoint blaming the actors of the transition who laid  the foundation of the current political system in the second half of  1970s – fi rst half of 1980s. Such an approach demonstrates radical  reevaluation of values since until quite recently the dominating belief in the public conscience in Spain and beyond treated the Spanish transition as a model type within the third wave transition  framework. The author does not agree with the negative appraisal of the transition which allowed Spain not only to avoid a new civil war  but to set up the regime of representative democracy for the first  time in its history. The transition politics certainly had weaknesses and limitations. The successor political actors had the opportunities  to remedy the situation by changing the legislation and practices but they did not do it since ruling as usual was easier. At the same time the Spanish transition experience compared to the present-day reality proves that even successful decisions work only for some time. New stages of societal development demand the  correction of previous and development of new pragmatic solutions  taking national interests into account. The issues which were not dominating the political discourse at the time of the transition and seemed to be solved (like monarchy vs. republic, conflict between staunch Catholics and secularists, evaluation of the past) were brought to the center of political struggles many  years after. The author concludes that it is incorrect to defi ne the  direct relation between the modern problematic zones of the Spanish society and the policy at the time of democratic transition.